Suicidal Ideation in Reg Cribb's play Last Cab to Darwin (2003) - Agung Trimulya; Muhd. Al-Hafizh (English Language and Literature, 2020)
This thesis is an analysis of a play written by Reg Cribb, entitled Last Cab to Darwin (2003). It explored the issue about suicidal ideation which is an irrational mindset by a person who think his lives is not useful for having a terminal illness and to what extent the character and setting contributed to identify the issue. This play  related to the concept of Death Instinct (thanatos) by Sigmund Freud. The uses of the theory is based on the interpretation of the text and context of the play. The result of this analysis show the causes of suicidal ideation by two groups. First is suffering. Second is hopelessness.